Papaya Seed Essential Oil Anti-Acne Cream and Its Effectiveness Against Staphylococcus epidermidis and Cutibacterium acnes - Fadiyah Aprilia; Ulfayani Mayasari (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Acne is a common skin disorder that affects people from all walks of life. One of the causes of acne is the bacteria Staphylococcus epidermidis and Cutibacterium acne. Papaya seeds are known to have antibacterial properties because they contain active compounds that inhibit bacterial growth. The main objective of this study was to determine the antibacterial activity of acne cream with the addition of papaya seed essential oil (Carica papaya L.) against Staphylococcus epidermidis and Cutibacterium acne bacteria. The method used in the production of essential oil was steam distillation, the antibacterial activity test was conducted using the disc diffusion method with concentrations of 10%, 20%, 30%, 40%, and 50%, and the cream activity test was conducted using the well method. The data analysis results were analyzed using analysis of variance (ANOVA). The results showed that papaya seed essential oil against Staphylococcus epidermidis bacteria at concentrations of 10%, 20%, 30%, 40%, and 50% was 7.7 mm, 13.1 mm, 16.3 mm, 18.7 mm, and 21.6 mm, respectively. Meanwhile, against Cutibacterium acne, the results were 4.6 mm, 6.4 mm, 9.9 mm, 12.1 mm, and 14.1 mm, respectively. Meanwhile, the inhibition zone results of papaya seed essential oil cream against Staphylococcus epidermidis bacteria at concentrations of 40% and 50% were 18.7 mm and 21.7 mm, respectively, while the inhibition zone of the cream against Cutibacterium acne bacteria was 12.8 mm and 14.1 mm. It can be concluded that the acne cream made from papaya seed essential oil has the potential to inhibit the growth of Staphylococcus epidermidis and Cutibacterium acne. A concentration of 50% proved to be the most effective in inhibiting the growth of acne-causing bacteria.